Kemitraan Pemerintah dan Lembaga Adat dalam Penanganan Kesehatan Ibu Hamil dan Melahirkan sebagai Good Governance Innovation di Komunitas Adat Karampuang Desa Tompbulu Kab. Sinjai - Karim, Syahrir; Wahdaniah (SOSIORELIGIUS, 2024)
Villages with traditional communities within them with all the uniqueness and character of their community life must be a special concern for the government. The government should be involved in developing and preserving customs, local wisdom, and existing cultural values. As is the case with Tompobulu village with the Karampuang traditional community within it, it is necessary to create a good partnership pattern between the government and customs. One of the main issues in this study is related to the partnership between the government and customs regarding the handling of pregnant women and childbirth in an effort to innovate Good Governance, especially at the village level. This study then found that a partnership had been established between the government and customs, although not yet optimally.